2019
DOI: 10.1002/ptr.6411
|View full text |Cite
|
Sign up to set email alerts
|

Studies on antioxidant, hepatoprotective, and vasculoprotective potential of Viola odorata and Wrightia tinctoria

Abstract: We have reported the antidyslipidemic, antihypertensive, and Ca++ channel blocking activities of Viola odorata (VO) and Wrightia tinctoria (WT). This study extends our understanding of their therapeutic potential by exploring the effects on biomarkers of hepatic and vascular dysfunction together with phytochemical standardization and antioxidant potential. Total phenolic compounds, total flavonoids content, and proanthocyanins of the methanolic extracts were identified using HPLC. Antioxidant capacity was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…It is used to treat various ailments such as cough, coryza, headache, pleurisy, pneumonia, throat irritation, and complex fever 41; 42; 43; 45 . It possesses various pharmacological properties and has been studied for its antipyretic 58 , anti-inflammatory 59 , antioxidant, vascular protective 60 , neuroprotective 61, antihypertensive, antidyslipidemic 62 , hepatoprotective 63 antitussive, anti-asthmatic 64 and antibacterial activity 65 .…”
Section: Discussionmentioning
confidence: 99%
“…It is used to treat various ailments such as cough, coryza, headache, pleurisy, pneumonia, throat irritation, and complex fever 41; 42; 43; 45 . It possesses various pharmacological properties and has been studied for its antipyretic 58 , anti-inflammatory 59 , antioxidant, vascular protective 60 , neuroprotective 61, antihypertensive, antidyslipidemic 62 , hepatoprotective 63 antitussive, anti-asthmatic 64 and antibacterial activity 65 .…”
Section: Discussionmentioning
confidence: 99%
“…The column was monitored at wavelength 280 nm. The mobile phase consisted of 2%(v/v) acetic acid (A) and methanol (B) and the gradient program was set according to the method described by Jamshed H et al with some modifications ( Jamshed et al, 2019 ). The gradient elution was started with 5% B increasing to 30% at 10 mins, then increased from 30% B to 100% B during the next 20 mins at a flow rate of 0.8 ml/min.…”
Section: Methodsmentioning
confidence: 99%
“…Medicinal plants with anti-inflammatory properties were selected from the previous literatures (Aleem et al, 2020;Jeewanthi et al, 2020;Jamshed et al, 2019) and potential compounds identified from the selected plants were used as ligands in this study. The 3D structures of the selected ligands namely 6 urs-12-en-24-oic acid (Figure 2a) and β-Amyrin ( Figure 2b) from Plumbago zeylanica, 10,12-Docasadiyndioic Acid ( Figure 2c) and 1(Ethynyltrimethylsilyl-2)-1-Chloro-2-Ethyl-2-methyl cyclopropane (Figure 2d) from Neolitsea cassia, and Androstane (Figure 2e) from Wrightia tinctoria was collected from Pubchem (http://pubchem.ncbi.nlm.nih.…”
Section: Preparation Of Ligandsmentioning
confidence: 99%